Pengaruh Tingkat Pendidikan, Pemahaman Akuntansi, dan Kesiapan Pelaku UMKM Terhadap Penerapan SAK EMKM Dalam Penyusunan Laporan Keuangan UMKM - Periska, Vera; Yanti., SE.,M.Ak; Rachpriliani., SE.,M.Ak, Awaliawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to evaluate and examine the effect of the educational level of Micro, Small and Medium Enterprises (UMKM) actors, accounting knowledge, and readiness on the use of Micro, Small, and Medium Entity Financial Accounting Standards (SAK EMKM) in compiling MSME financial reports in districts. Karawang. This study uses a quantitative methodology with primary data collection. The sample for this study only consisted of SMEs based in Karawang Regency. The number of samples for this research is one hundred respondents. This research focuses on MSMEs in Karawang Regency. By using PLS and SmartPLS 3.0, analyze the relationship between the dependent and independent variables. The findings of this study indicate that the level of education, accounting knowledge, and readiness of MSME actors have a positive and significant effect on the implementation of SAK EMKM. Keywords: Effect of education level, understanding of accounting, readiness of MSME actors, application of SAK EMKM